Pengaruh Populasi Bibit Sistem Tanam Tegel Penanaman Musim Tanam II Terhadap Pertumbuhan Dan Produktivitas Padi (Oryza sativa L) - Suharno Suharno; Fitria Isnayanti (Universitas Muhammadiyah Purworejo, 2018)
This study aims to determine the effect of plant populations on the growth and productivity of rice (Oryza sativa L). The research was conducted in Sumberharjo Village, Prambanan District, Sleman Regency, Yogyakarta Special Region. The research period was during planting season II, March-July 2017. The research method used was factorial completely randomized block design (RAKL), the first factor was three levels, namely the spacing of 20cm x 20cm (T1), 25cm x 25cm (T2), and 30cm x 30cm (T3). The second factor is three levels, namely the number of seeds per clump of two seeds (B1), four seeds (B2), six seeds (B3). The treatment combinations are as follows: T1B1; T1B2; T1B3; T2B1; T2B2; T2B3; T3B1; T3B2; T3B3. The results showed that the combination of the spacing factor (T) and the number of seeds (B) had a very significant effect on the growth of rice plants, the yield of harvested dry grain (GKP), and had a significant effect on the yield of milled dry grain (GKG) The treatment of spacing factor (T) has a very significant effect on the growth of rice plants, yields of harvested dry grain (GKP) and yields of milled dry unhulled rice (GKG). Treatment factor number of seeds (B), had a significant effect on the growth of rice plants, had no significant effect (TN) on yields of harvested dry grain (GKP) and yields of milled dry unhulled rice (GKG). The treatment combination showed the best growth at (T3 B3) with average biomass of 69.6 grams / 5 clumps, the yield of dry unhulled rice at (T1 B3) averaged 6.57 t / ha, and the yield of the milled dry grain at (T1 B3) 5.72t / ha on average. The treatment of spacing factor (T) showed the best growth at (T3) biomass with an average of 60.5 g / 5 clumps, dry unhulled grain at (T1) an average of 6.39 t / ha, and milled dry unhulled rice at (T1) an average of 6.39t / ha. The treatment of the number of seeds (B), showed the best growth at (B3) biomass with an average of 54.83g / 5 clumps, harvested dry grain at (B3) an average of 5.93t / ha, and milled dry grain at (B3). ) an average of 5.21t / ha. The combination of the spacing factor treatment with the number of seeds showed no interaction.